If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = 77 + -7x Reorder the terms: 7 + 5x = 77 + -7x Solving 7 + 5x = 77 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 7 + 5x + 7x = 77 + -7x + 7x Combine like terms: 5x + 7x = 12x 7 + 12x = 77 + -7x + 7x Combine like terms: -7x + 7x = 0 7 + 12x = 77 + 0 7 + 12x = 77 Add '-7' to each side of the equation. 7 + -7 + 12x = 77 + -7 Combine like terms: 7 + -7 = 0 0 + 12x = 77 + -7 12x = 77 + -7 Combine like terms: 77 + -7 = 70 12x = 70 Divide each side by '12'. x = 5.833333333 Simplifying x = 5.833333333
| 7x-2x=12 | | 3u+20=8u | | 6x+13=-9-10 | | 7g-15=g-3 | | 2x+x^2+144=0 | | 85-3x=2x+10 | | (4-2k+3l)+(2-3k-2l)= | | 135-2x=34x+15 | | -104-7x=10x+15 | | 2x+12=-38-8x | | y=-32x^2-6x | | y=-32x^2-6x | | y=-32x^2-6x | | 2x^2+30=0 | | 14-10x=74-24x | | -37-7x=7x+20 | | (7z-3)-(4z-11)=47 | | 6t-5=2t-5 | | 266-6x=39x+21 | | 3r+6=18 | | 7x(-2x+3)=0 | | 6x(4x+3)=0 | | 2(2)-3y=-9 | | -50+x=-10 | | 40x-6=9 | | -4(x+3)=x+8 | | 6x(4x-1)=0 | | 5x-10x=x-12 | | 172-6x=6x+16 | | -(-2x)=(-88) | | 2(x+4)=5x-1 | | 6p+12=4p |